Bacteris and bacteriophages in fish ponds fertilized with septage - Choudry, Khadim Hussain; Chongrak Polprasert; Watanabe, Yoshimasa; Lohani, B.N.; Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1981)
Septage, a highly polluting organic matter with off- ensive odour and a variety of micro-organisms was tested for its potential as fertilizer to fish ponds for the production of phytoplankton, for fish culture. Ten out of sixteen pilot scale earth fish ponds, operated as a non-flow through system, each measuring 20 m x 10 m x 1.3 m : length x width x depth, were used. Different stocking densities of Tilapia Nilotic i.e. , 3, 9 and 15 fish/m2 were used in triplicate and the ponds were fed with variable organic septage loadings (33.33, 50 and 100 kg COD/ha/day) throughout the experiment . A control pond without septage feeding was operated in parallel and stocked with 5 fish/m2 The fish yields obtained at the end of experiment were 3.6, 5.5, 5.8 and 0.3 tons/ha from ponds stocked with 3, 9, 15 and 5 fish/m2 Results of micro-biological investigations of fish ponds were compared with the "threshold concentration" recommended by BURAS (1979), which showed that the fish reared in the system, using organic septage loadings upto 100 kg COD/ha/day would have little chance for bacterial penetration to the fish tissue.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Fish ponds -- Fertilization; Bacteriophages